THE “HOUSE OF GOD”: THE ROLE OF RELIGION AND LITURGY IN THE TRANSFORMATION OF SACRED BUILDINGS (Religious dialogue and cooperation, 2024)
The paper wishes to analyse the religious buildings, with special attention to the Christianones, considering their transformation due to liturgical and religious reasons. The aim of theresearch relates to the needs of restoration and conservation of the buildings. The restorationand conservation work compels the understanding of all the historical construction phases of thebuilding itself, and the reasons for them, in order to plan a good project, able to respect their real“authenticity”, according to the Nara charter, established by ICOMOS (International Council ofMonuments and Sites) in 1994. The Nara document is inspired by the Venice Charter, approved in1964 and adopted by ICOMOS in 1965, where, in chapter 3, is stated that: “The intention in conservingand restoring monuments is to safeguard them no less as works of art than as historical evidence.”Restoration refers to the conservation of the historical evidence plus the historical meaningof the building. The traces, even if hidden, of the past, related to different conceiving of the building,must be transferred to the future and made available and comprehensible for everyone. The valorisationof the building, as it is defined by the Italian law of 2004 is a tool for the dissemination ofculture, because the culture must be accessible to everyone. The religion and the places devoted tosharing spiritual values, in any geographical and political position and at any time, focusing onintercultural dialogue in a peaceful environment, must be accepted and the work of restorationmust be connected with the transformation in order to ensure the respect of the cultural values ofreligious places. Starting from the re-transformation of Hagia Sophia in Istanbul, from Museum toMosque and the reception of the transformation from the history and history of art internationalenvironment, the paper has the intention to offer an overview, through different examples relatedto diverse times and places, of the role of the religion and liturgy in the transformation of the houseof god and the connection with the cultural environment considering that the transformation hasa strong connection with the restoration activities both on the decorative elements and spatialdimension of the religious buildings and their environment.
Keywords: Religious Building; Multy-Faith; Liturgy; Interreligious dialogue; religious and Cultural Heritage Valorisation